Conceptos para el estudio del agro latinoamericano: campesinos y agricultores familiares - Eloy Gómez-Pellón (Antípoda: Revista de Antropología y Arqueología)
The vast agricultural landscape of Latin America is home to more than 17 million agricultural enterprises, all sharing a common characteristic: family-based social organization of labor. These production units span a spectrum from subsistence peasant agriculture to entrepreneurial family farming, with an intermediate type often referred to as transitional family farming. Today, the term family farmers is generally used to describe the social actors within this typology, gradually replacing the older term peasants, although the latter remains relevant in certain contexts. This article explores the reasons behind the gradual shift from the term peasantry to family farming and to assess the theoretical and practical implications of this shift in the Latin American context. The methodology involves an analysis and comparison of the concept of the peasantry as understood by various historical and ideological schools: agrarian scholars, Russian populists, Russian anarchists (e.g., Kropotkin), Marxists, reformist Marxists (e.g., Luxemburg, Bukharin), and social agronomists (e.g., Bulgakov, Chayanov), who represent the old tradition of peasant studies. It also reviews the contributions of the new American tradition in peasant studies (e.g., Kroeber, Redfield) and examines the relevant literature on Latin American family farming (e.g., Schejtman, Maletta, Schneider). The study concludes by underscoring the consolidation of the concept of family farming and its significance for policy agendas at both governmental and supranational levels. Family farming plays a crucial role in surplus production, food security, environmental sustainability, and rural employment generation in Latin America, making it an essential area for continued attention and support.